The effect of stone column geometry on soft soil bearing capacity - Hamzh, A. (Taylor and Francis Ltd., 2022)
Stone columns are one of the common types of ground improvement methods that applied to reduce the settlement and increase the stability of structures. This paper focuses on the non-uniform diameters of the stone column and aimed at providing some practical insights into the design by reducing the constructing material of the stone column with increasing the bearing capacity of the soft soil. In this study, two dimensional (2D) Finite Element analyses through PLAXIS 2D were performed to investigate the bearing capacity of uniform and non-uniform stone columns in soft soil. A Mohr-Coulomb constitutive soil model was adopted in the numerical analyses. The non-uniform stone columns modelling by creating two different diameters and lengths. The upper diameter d1 was always larger than the lower half diameter d2 with investigated ratio d2: d1 of 1:2, 1:4 and 1:5. The columns were 10 m long but varied in diameter length with nine different length ratios (l1: l2). By comparing between uniform and non-uniform shapes, one can determine the optimum columnâs design. The highest bearing capacity obtained by the non-uniform stone column was one with the d2:d1 ratio equals to 1:5. The most economical shape for the stone column (the least volumes used to construct stone columns) was achieved at a ratio of d2:d1 = 1:2 and a length ratio of l1:l2 = 3:7. Â© 2019 Informa UK Limited, trading as Taylor & Francis Group.